2020
DOI: 10.3390/pr8111458
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Biomass and Lipid Productivities of Scenedesmus sp. Cultivated in the Wastewater of the Dairy Industry

Abstract: Microalgae are photoautotrophic microorganisms capable of producing compounds with potential bioenergetic applications as an alternative energy source due to the imminent exhaustion of fossil fuels, their impact on the environment, and the constant population increase. The mass cultivation of these microorganisms requires high concentrations of nutrients, which is not profitable if analytical grade culture media are used. A viable alternative is the use of agro-industrial wastewater, due to the metabolic flexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Volumetric, areal and lipid productivity of selected freshwater microalgae: The biomass production of microalgae is a mere function of the instantaneous growth rate and algal cell concentration in culture (Daniel and Srivastava 2016). In the present study, different microalgae showed variation in biomass productivity which can be justified as productivity of microalgae is also influenced by the microalgal strain used and the characteristics of the environment, where it grows (Mercado et al 2020). Moreover, lipid productivity of microalgae also varied among species as it depends on biochemical composition of microalgae, nutrient content of culture media and different stress factors.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…Volumetric, areal and lipid productivity of selected freshwater microalgae: The biomass production of microalgae is a mere function of the instantaneous growth rate and algal cell concentration in culture (Daniel and Srivastava 2016). In the present study, different microalgae showed variation in biomass productivity which can be justified as productivity of microalgae is also influenced by the microalgal strain used and the characteristics of the environment, where it grows (Mercado et al 2020). Moreover, lipid productivity of microalgae also varied among species as it depends on biochemical composition of microalgae, nutrient content of culture media and different stress factors.…”
Section: Resultsmentioning
confidence: 61%
“…Scenedesmus sp. resulted about 350.81 ± 33.05 mg g −1 of lipid productivity in standard BG11 culture medium (Mercado et al 2020). Based on the outcomes of the current study, Nannochloropsis sp., Monoraphidium sp., and Scenesdesmus sp.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…However, as environmental problems such as global warming and harmful gas emission are growing severe, development of environment friendly and sustainable biotechnology is direly necessary. Accordingly, the development of bioconversion technology is being activated by using microorganisms and biomass resources [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%